Carolina Coronado en su biografía. La construcción de una imagen: mecenazgo masculino y apuntes biográficos - Estefanía Cabello (Cuadernos de Ilustración y Romanticismo)
In the first edition of Carolina Coronado’s Poesías (1843), the philologist and polymath Juan Eugenio Hartzenbusch creates a prologue that introduces and is attached to the literary work of the extremenian author, granting her a voice and confirming the author as a relevant writer of the time. In 1852, the work was edited again along with Hartzenbusch’s prologue plus a biographic note signed by another polymath of that age, Ángel Fernández de los Ríos; just five years later, Castelar reproduces a written portrait of Coronado in La Discusión. This study examines the role that these paratexts play on the construction of Carolina Coronado’s image and, in this sense, the way they help determinate the institutionalization of Coronado within a literary canon in mid-19th-century Spanish literature.